2021
DOI: 10.4236/jbm.2021.95011
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Nursing Staff on Postoperative Pain: The Case of the Laquintinie Hospital in Douala, Cameroon

Abstract: Background and objective: Pain is a major concern in the surgical environment, but its management remains insufficient due to several factors related to the nursing staff, the organization of the structure or the patient himself. The objective of this study was to assess the knowledge of the nursing staff on postoperative pain at the Laquintinie Hospital in Douala. Methodology: This was a cross-sectional study carried out at the Laquintinie Hospital in Douala from September to December 2018. Participants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…This is in the same line with Reyad et al, (2022) who reported that most of studied nurses' ages ranged between 20 to30 years old. On the other hand, Houmkoua et al, (2021) who found that about one third of nurses were aged from 30 to35 years old.…”
Section: The Aim Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This is in the same line with Reyad et al, (2022) who reported that most of studied nurses' ages ranged between 20 to30 years old. On the other hand, Houmkoua et al, (2021) who found that about one third of nurses were aged from 30 to35 years old.…”
Section: The Aim Of This Studymentioning
confidence: 99%
“…Finally, ongoing monitoring provides opportunities to detect complications at earlier stages. (Houmkoua, Mbouemboue, Oumarou, Essome, & Balep, 2021).…”
Section: Introductionmentioning
confidence: 99%